2014
DOI: 10.3389/fpls.2014.00356
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the proteomic profile of rice meiocytes during early meiosis

Abstract: Transfer of genetic traits from wild or related species into cultivated rice is nowadays an important aim in rice breeding. Breeders use genetic crosses to introduce desirable genes from exotic germplasms into cultivated rice varieties. However, in many hybrids there is only a low level of pairing (if existing) and recombination at early meiosis between cultivated rice and wild relative chromosomes. With the objective of getting deeper into the knowledge of the proteins involved in early meiosis, when chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…Recently, a proteomic analysis for early rice male meiocytes was published, in which 1316 expressed proteins were identified (Collado‐Romero et al ., ). Comparative analysis with our phosphoproteomic data revealed that 414 meiocytes expressed proteins were phosphorylated (Figure a and Table S6).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a proteomic analysis for early rice male meiocytes was published, in which 1316 expressed proteins were identified (Collado‐Romero et al ., ). Comparative analysis with our phosphoproteomic data revealed that 414 meiocytes expressed proteins were phosphorylated (Figure a and Table S6).…”
Section: Resultsmentioning
confidence: 97%
“…Further analysis found that, except the meiosis-related proteins listed in the Table 1, additional 15 phosphorylated proteins were annotated as chromatin-associated ones (Table S4). Interestingly, five phosphorylated proteins, LOC_Os02g01740 (a putative helicase), LOC_Os03g06220 (a DEAD-box ATP-dependent RNA helicase), LOC_Os02g36710 (a SET-domaincontaining protein), LOC_Os03g52310 (a transposon protein) and LOC_Os04g18090 (Histone H1), were exclusively identified in early prophase I stage during meiosis (Collado-Romero et al, 2014). Secondly, 117 phosphorylated proteins were classified into protein synthesis group, including ribosomal protein, initiation and elongation factor sub-groups, in which 52 were identified in rice early meiosis (Table S2 and S6).…”
Section: Meiotic and Putatively Meiotic Proteinsmentioning
confidence: 99%
“…In fact, for some wheat genotypes as those carrying the Ph1 deletion, meiosis is not synchronized 43 , making the identification of each meiosis stage even more complicated. In addition, and as far as we know, although there are some massive approaches to study meiosis using transcriptomics and proteomics in cereals like maize [44][45][46] , rice 47,48 and other plants 49 , the only massive transcriptomic study covering the whole meiosis process in wheat anthers was performed by Crismani and colleagues 23 , using the Affymetrix GeneChip Wheat Genome Array. Recent studies have examined gene expression in wheat meiotic anthers using RNA-seq 31,38 .…”
Section: Discussionmentioning
confidence: 99%
“…To detect potential KAC proteins involved in rice meiosis, we next conducted a comparison analysis between the rice meiocyte proteome reported previously (Collado-Romero et al, 2014) and the RAM lysine acetylome here. We found that 357 acetylated proteins, representing over half of the total identified in the RAM, were present in rice meiocytes (Figure 5a and Table S6).…”
Section: Lysine Acetylation Of Non-histone Proteins Associated With Mmentioning
confidence: 99%